A biomimetic dual-ion concentration battery based on polyelectrolyte hydrogel
By adopting a bionic dual-ion concentration-difference battery structure with polyelectrolyte hydrogel film stack in the electrochemical energy storage device, the problems of existing electrochemical energy storage devices in terms of safety, environmental friendliness, sustainability and voltage stability are solved, and efficient and stable high-power output is achieved, and biocompatibility and degradability are achieved.
Patent Information
- Application Number
- CN202210835642.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-07-15
- Publication Date
- 2025-04-18
- Estimated Expiration
- 2042-07-15
AI Technical Summary
The existing electrochemical energy storage devices have limitations in terms of safety, environmental friendliness, sustainability, capacity and power density, and are affected by temperature and humidity and the output voltage is unstable.
A bionic dual-ion concentration difference battery based on polyelectrolyte hydrogel is used to stack polyanionic electrolyte hydrogel film and polycationic electrolyte hydrogel film as power generation layers, and polyhydroxy compounds such as sodium alginate, chitosan quaternary ammonium salt, polyvinyl alcohol and glycerol are used to connect and fix the polymer chain skeleton through intermolecular hydrogen bonds to form a stable battery structure.
It realizes that the battery has a stable output voltage under 10-50°C and 0-85% humidity, and has good voltage output stability. It can also make the output voltage reach more than 800V by stacking the power generation layer in series. It has good biocompatibility and degradability, making it suitable for large-scale production.
Smart Images

Figure CN115189006B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of ion concentration difference batteries, and more specifically to a bionic dual ion concentration difference battery based on polyelectrolyte hydrogel. Background Art
[0002] With the depletion of traditional non-renewable energy and the increasingly serious environmental pollution problem, the development of renewable energy such as solar energy, wind energy, and tidal energy has become an inevitable trend, and people's requirements for electrochemical energy storage technology and devices have also increased accordingly. Traditional electrochemical energy storage devices mainly include secondary batteries and supercapacitors represented by lithium-ion batteries, which have been widely used in commercial electronic products, energy storage systems and other important occasions. However, their further development is still limited by issues such as safety, environmental friendliness, sustainability, capacity and power density. In the 21st century, electrochemical energy storage devices are constantly developing in the direction of miniaturization, flexibility, intelligence and high integration to meet the functional requirements of specific application scenarios.
[0003] The electric eel generates a discharge voltage of up to 860V and a current of 1A with its tens of thousands of electric cells. This strong discharge ability has attracted people's attention. The discharge principle is that there is natural Na inside and outside the electric cells. + / K + The concentration difference, and the ion-selective channels on the front and back cell membranes make K + Outflow and Na + Flowing into the cell, therefore, one electrocyte can generate a voltage of 150mV. Based on this, people have tried to simulate the structure and discharge mechanism of the electric eel to develop advanced energy storage devices with high output voltage and specific functions (such as transparency, biocompatibility and flexibility) to provide safer, more efficient and uninterrupted high-power output for portable, wearable and stretchable devices. So far, although electrochemical energy storage devices inspired by electric eels have begun to appear, such as the Chinese patent CN113150346A that discloses a nanogenerator made of a double-layer electrolyte membrane prepared from a polyanion / cation membrane as a power generation layer, the generator needs to be used under specific temperature and humidity conditions, is greatly affected by the use environment and has unstable output voltage. Summary of the invention
[0004] Based on the above-mentioned technical problems existing in the prior art, the present invention provides a bionic dual-ion concentration battery based on polyelectrolyte hydrogel. The battery can stably output voltage and is not affected by external temperature and humidity by stacking specific polycationic electrolyte hydrogel films and polyanion electrolyte hydrogel films as power generation layers. It has good biocompatibility and degradability and is suitable for large-scale production.
[0005] In order to achieve the above object, the technical solution of the present invention is as follows:
[0006] A bionic dual-ion concentration cell based on polyelectrolyte hydrogel comprises a battery cell, wherein the battery cell comprises a first current collector and a second current collector, an intermediate layer is arranged between the first current collector and the second current collector, and the intermediate layer comprises at least one group of stacked polyanion electrolyte hydrogel films and polycation electrolyte hydrogel films; wherein the polycation electrolyte hydrogel film is made by the following method: glycerol and deionized water are mixed, then polyvinyl alcohol is added until completely dissolved, then chitosan quaternary ammonium salt is added and mixed, and a film is formed in a mold; and the polyanion electrolyte hydrogel film is made by the following method: glycerol and deionized water are mixed, polyvinyl alcohol is added until completely dissolved, then sodium alginate is added and mixed, and a film is formed in a mold.
[0007] In the above technical scheme, the raw materials for making the polycationic electrolyte hydrogel film and the polyanionic electrolyte hydrogel film are polyhydroxy compounds - chitosan quaternary ammonium salt, sodium alginate, polyvinyl alcohol and glycerol, wherein polyvinyl alcohol and glycerol connect and fix the polymer chain skeleton of chitosan quaternary ammonium salt / sodium alginate through intermolecular hydrogen bonds, and the polyhydroxy compounds have strong hydrophilicity and good water absorption, and sufficient water is added during the preparation process, which can provide a stable solution environment, which is conducive to the continuous and stable release of ions in chitosan quaternary ammonium salt / sodium alginate, so that the manufactured battery is not affected by external temperature and humidity, and maintains voltage stability under the conditions of 10-50°C and relative air humidity of 0-85%.
[0008] In some embodiments, the free Cl generated in the polycationic electrolyte hydrogel film - The concentration is 0.0001~0.5mol / L.
[0009] In some embodiments, the free Na generated in the polyanion electrolyte hydrogel film + The concentration is 0.0001~0.5mol / L.
[0010] In some embodiments, in the preparation of the polycationic electrolyte hydrogel film, the mass ratio of the glycerol, water, polyvinyl alcohol and chitosan quaternary ammonium salt is 700:200:100:1-20; in the preparation of the polyanionic electrolyte hydrogel film, the mass ratio of the glycerol, water, polyvinyl alcohol and sodium alginate is 700:200:100:1-20.
[0011] In some embodiments, the preparation of the polycationic electrolyte hydrogel film comprises the following steps:
[0012] Propylene glycol and water are mixed evenly, and then polyvinyl alcohol is added, and the polyvinyl alcohol is completely dissolved by stirring at 100° C., and then chitosan quaternary ammonium salt is added, and the chitosan quaternary ammonium salt is completely dissolved by stirring at 100° C. to obtain a mixed solution; the mixed solution is added into a mold while hot, and cooled to obtain the polycationic electrolyte hydrogel film.
[0013] In some embodiments, the preparation of the polyanion electrolyte hydrogel film comprises the following steps:
[0014] Propylene glycol and water are mixed evenly, and then polyvinyl alcohol is added, and the mixture is stirred at 100° C. to completely dissolve the polyvinyl alcohol. Then sodium alginate is added, and the mixture is stirred at 100° C. to completely dissolve the sodium alginate to obtain a mixed solution. The mixed solution is added into a mold while hot, and cooled to obtain the polyanion electrolyte hydrogel film.
[0015] In some embodiments, the number average molecular weight of the polyvinyl alcohol is 100,000 to 200,000.
[0016] In some embodiments, the first current collector and the second current collector are respectively one of aluminum foil, copper foil, gold foil, zinc foil, platinum sheet, graphite felt electrode, and conductive carbon tape.
[0017] In some embodiments, the size of the polycationic electrolyte hydrogel film is 1 cm×2 cm×0.1-2 cm.
[0018] In some embodiments, the size of the polyanion electrolyte hydrogel film is 1 cm×2 cm×0.1-2 cm.
[0019] In some embodiments, the sizes of the first current collector and the second current collector are 3 cm×2 cm×0.5-1.5 cm, respectively.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] like Figure 1 As shown, the present invention uses a specific polyanion electrolyte hydrogel film and a polycation electrolyte hydrogel film stacked as a power generation layer. The sodium alginate, chitosan quaternary ammonium salt, polyvinyl alcohol and glycerol used in the polyanion / cation electrolyte hydrogel film are all polyhydroxy compounds. On the one hand, polypropylene alcohol and glycerol are connected and fixed to the polymer chain skeleton in the chitosan quaternary ammonium salt or sodium alginate through strong hydrogen bonds, so that the polyanion / cation electrolyte hydrogel has excellent structural stability; on the other hand, hydroxyl groups are hydrophilic groups, and the hydrogel made of polyhydroxy compounds as raw materials has good water absorption, can provide a stable solution environment, and is conducive to the Cl in the chitosan quaternary ammonium salt - and Na in sodium alginate +The continuous and stable release of ions enables the battery to output a stable voltage.
[0022] In addition, during the preparation of polyanion / cation electrolytes, a stable solution environment is formed inside the polyanion / cation electrolyte hydrogel film due to the addition of water. When the humidity in the environment is low, the hydrophilicity of the hydroxyl groups of the compounds can prevent water loss in the hydrogel and maintain the solution environment of the hydrogel. When the humidity in the environment is high, based on the water absorption limit of the hydrogel, the solution environment inside the hydrogel can be stabilized, which is beneficial to ion migration and transport, thereby ensuring that the power generation layer composed of the polyanion / cation electrolyte hydrogel can continuously release a stable concentration of free ions, thereby stabilizing the output voltage of the battery.
[0023] The battery provided by the present invention can stably output a voltage of more than 0.9V in an environment with a temperature of 10-50°C and a humidity of 0-85%, and the voltage output stability is good. Furthermore, the output voltage of the battery can reach more than 800V by stacking the middle layer of power generation in series.
[0024] The battery of the present invention has a wide source of raw materials, low cost, good biocompatibility and degradability, is easy to mass produce, and is expected to provide cleaner, safer, more efficient and uninterrupted high-power output for portable, wearable and stretchable devices. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 Schematic diagram of dual ion concentration difference of stacked polyanion / cation electrolyte hydrogel film;
[0026] Figure 2 is a schematic structural diagram of a battery cell of Example 1;
[0027] Figure 3 This is a schematic diagram of the structure of several battery cells connected in series in Example 2;
[0028] Figure 4 is the open circuit voltage value of the battery cell of Example 1 at different temperatures;
[0029] Figure 5 is the open circuit voltage value of the battery cell of Example 1 under different air relative humidity;
[0030] Among them, 1 is the first current collector, 2 is the second current collector, 3 is the intermediate layer, 31 is the polycationic electrolyte hydrogel film, and 32 is the polyanionic electrolyte hydrogel film. DETAILED DESCRIPTION
[0031] Many specific details are set forth in the following description to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways than those described herein, and those skilled in the art can make similar modifications without violating the connotation of the present invention, so the present invention is not limited to the specific implementation disclosed below.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0033] In the specific embodiments of the present invention, unless otherwise specified, the chemical reagents, raw materials and equipment used can be purchased from the market or prepared by any existing publicly available method.
[0034] In the raw materials of the following polyanionic electrolyte hydrogel and polycationic electrolyte hydrogel, the polyvinyl alcohol is polyvinyl alcohol with a number average molecular weight of 100,000; and the chitosan quaternary ammonium salt is 2,3-epoxypropyltrimethylammonium chloride chitosan.
[0035] The preparation of the polycationic electrolyte hydrogel film 31 comprises the following steps:
[0036] 21g of glycerol was mixed with 6g of water, stirred evenly, then 3g of polypropylene alcohol was added, heated to 100°C, stirred to completely dissolve the polypropylene alcohol, then 0.45g of chitosan quaternary ammonium salt was added, stirred at 100°C to completely dissolve the chitosan quaternary ammonium salt, and a uniform mixed solution was obtained; the obtained mixed solution was added to a mold while hot, cooled to room temperature, and a polycationic electrolyte hydrogel film was obtained. The polyanionic electrolyte hydrogel film was cut to a size of 1cm×2cm×0.2cm for later use.
[0037] The preparation of the polyanion electrolyte hydrogel film 32 comprises the following steps:
[0038] 21g of glycerol and 6g of water were mixed and stirred evenly, then 3g of polypropylene alcohol was added, heated to 100°C, stirred to completely dissolve the polypropylene alcohol, and then 0.45g of sodium alginate was added, and stirred at 100°C to completely dissolve the sodium alginate to obtain a uniform mixed solution; the obtained mixed solution was added to a mold while hot, and cooled to room temperature to obtain a polyanion electrolyte hydrogel film. The polyanion electrolyte hydrogel film was cut to a size of 1cm×2cm×0.2cm for later use.
[0039] Example 1
[0040] like Figure 2As shown, a bionic dual-ion concentration cell based on polyelectrolyte hydrogel includes a battery cell, which includes a first current collector 1, an intermediate layer 3 and a second current collector 2 from top to bottom, the intermediate layer includes a stacked polycation electrolyte hydrogel film 31 and a polyanion electrolyte hydrogel film 32, the first current collector 1 and the second current collector are gold foils, both with a size of 3cm×2cm×0.5cm. After testing, the battery cell of this embodiment has an output voltage of up to 1.125V at a temperature of 25°C and a humidity of 25%, and a current density of 0.85mA / cm 2 The maximum output power can reach 0.09W / m 2 .
[0041] The battery cells manufactured in this embodiment were tested under different temperature and humidity environments. The specific test method is: voltage output test was performed under 25% relative humidity and at different temperatures. The test results are shown in FIG. Figure 4 As shown; at a temperature of 25°C, the voltage output test was carried out at different relative humidity. The test results are shown in Figure 5 shown.
[0042] Example 2
[0043] The battery of this embodiment can be formed by connecting multiple battery cells in series, such as Figure 3 As shown, a plurality of battery cells are connected in series from left to right through the first current collector 1 or the second current collector 2, and each battery cell is in a sandwich structure, so that the obtained battery can stably output a voltage of 800V.
[0044] The technical features of the above-described embodiments may be arbitrarily combined. To make the description concise, not all possible combinations of the technical features in the above-described embodiments are described. However, as long as there is no contradiction in the combination of these technical features, they should be considered to be within the scope of this specification.
[0045] The above-mentioned embodiments only express several implementation methods of the present invention, and the descriptions thereof are relatively specific and detailed, but they cannot be understood as limiting the scope of the invention patent. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, and these all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. A bionic dual-ion concentration battery based on polyelectrolyte hydrogel, characterized in that: The invention comprises a battery cell, wherein the battery cell comprises a first current collector and a second current collector, an intermediate layer is arranged between the first current collector and the second current collector, and the intermediate layer comprises at least one group of stacked polyanion electrolyte hydrogel films and polycation electrolyte hydrogel films; wherein the polycation electrolyte hydrogel film is made by the following method: glycerol and deionized water are mixed, polyvinyl alcohol is added until completely dissolved, chitosan quaternary ammonium salt is added and mixed, and a film is formed in a mold; and the polyanion electrolyte hydrogel film is made by the following method: glycerol and deionized water are mixed, polyvinyl alcohol is added until completely dissolved, sodium alginate is added and mixed, and a film is formed in a mold.
2. The bionic dual-ion concentration cell based on polyelectrolyte hydrogel according to claim 1, characterized in that: In the polycationic electrolyte hydrogel film, the free Cl - The concentration is 0.0001~0.5mol / L.
3. The bionic dual-ion concentration cell based on polyelectrolyte hydrogel according to claim 1, characterized in that: In the polyanion electrolyte hydrogel film, the free Na + The concentration is 0.0001~0.5mol / L.
4. The bionic dual-ion concentration cell based on polyelectrolyte hydrogel according to claim 1, characterized in that: In the preparation of the polycationic electrolyte hydrogel film, the mass ratio of the glycerol, water, polyvinyl alcohol and chitosan quaternary ammonium salt is 700:200:100:1-20; in the preparation of the polyanionic electrolyte hydrogel film, the mass ratio of the glycerol, water, polyvinyl alcohol and sodium alginate is 700:200:100:1-20.
5. The bionic dual-ion concentration cell based on polyelectrolyte hydrogel according to claim 1, characterized in that: The preparation of the polycationic electrolyte hydrogel film comprises the following steps: Propylene glycol and water are mixed evenly, and then polyvinyl alcohol is added, and the polyvinyl alcohol is completely dissolved by stirring at 100° C., and then chitosan quaternary ammonium salt is added, and the chitosan quaternary ammonium salt is completely dissolved by stirring at 100° C. to obtain a mixed solution; the mixed solution is added into a mold while hot, and cooled to obtain the polycationic electrolyte hydrogel film.
6. The bionic dual-ion concentration cell based on polyelectrolyte hydrogel according to claim 1, characterized in that: The preparation of the polyanion electrolyte hydrogel film comprises the following steps: Propylene glycol and water are mixed evenly, and then polyvinyl alcohol is added, and the mixture is stirred at 100° C. to completely dissolve the polyvinyl alcohol. Then sodium alginate is added, and the mixture is stirred at 100° C. to completely dissolve the sodium alginate to obtain a mixed solution. The mixed solution is added into a mold while hot, and cooled to obtain the polyanion electrolyte hydrogel film.
7. The bionic dual-ion concentration cell based on polyelectrolyte hydrogel according to claim 1, characterized in that: The first current collector and the second current collector are respectively one of aluminum foil, copper foil, gold foil, zinc foil, platinum sheet, graphite felt electrode, and conductive carbon tape.
8. The bionic dual-ion concentration cell based on polyelectrolyte hydrogel according to claim 1, characterized in that: The size of the polycation electrolyte hydrogel film is 1 cm×2 cm×0.1-2 cm.
9. The bionic dual-ion concentration cell based on polyelectrolyte hydrogel according to claim 1, characterized in that: The size of the polyanion electrolyte hydrogel film is 1 cm×2 cm×0.1-2 cm.
Citation Information
Patent Citations
Double-layer polyelectrolyte membrane
CN113150346A
Polyelectrolyte hydrogel based on unzipping effect as well as preparation method and application of polyelectrolyte hydrogel
CN114702694A
Forward osmosis system with hydrogel used as draw solution
CN203668144U